Interindividual Contacts and Carriage of Methicillin-Resistant Staphylococcus aureus: A Nested Case-Control Study. (20th April 2015) - Obadia, Thomas; Opatowski, Lulla; Temime, Laura; Herrmann, Jean-Louis; Fleury, Éric; Boëlle, Pierre-Yves; Guillemot, Didier
<x content-type="archive" xml:space="preserve">Abstract</x> BACKGROUND Reducing the spread of multidrug-resistant bacteria in hospitals remains a challenge. Current methods are screening of patients, isolation, and adherence to hygiene measures among healthcare workers (HCWs). More specific measures could rely on a better characterization of the contacts at risk of dissemination. OBJECTIVE To quantify how close-proximity interactions (CPIs) affected Staphylococcus aureus dissemination. DESIGN Nested case-control study. SETTING French long-term care facility in 2009. PARTICIPANTS Patients (n=329) and HCWs (n=261). METHODS We recorded CPIs using electronic devices together with S. aureus nasal carriage during 4 months in all participants. Cases consisted of patients showing incident S. aureus colonization and were paired to 8 control patients who did not exhibit incident colonization at the same date. Conditional logistic regression was used to quantify associations between incidence and exposure to demographic, network, and carriage covariables. RESULTS The local structure of contacts informed on methicillin-resistant S. aureus (MRSA) carriage acquisition: CPIs with more HCWs were associated with incident MRSA colonization in patients (odds ratio [OR], 1.10 [95% CI, 1.04–1.17] for 1 more HCW), as well as longer CPI durations (1.03 [1.01–1.06] for a 1-hour increase). Joint analysis of carriage and contacts showed increased carriage acquisition in case of CPI with another colonized individual (OR, 1.55 [1.14–2.11] for 1 more HCW). Global network measurements did not capture associations between contacts and carriage. CONCLUSIONS Electronically recorded CPIs inform on the risk of MRSA carriage, warranting more study of in-hospital contact networks to design targeted intervention strategies. Infect. Control Hosp. Epidemiol. 2015;36(8):922–929